Large-Scale Group Decision-Making with Uncertain and Behavioral Considerations Methods and Applications - Wu, Tong.; Liu, Xinwang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book investigates in detail large-scale group decision-making (LSGDM) problem, which has gradually evolved from the traditional group decision-making problem and has attracted more and more attention in the age of big data. Pursuing a holistic approach, the book establishes a fundamental framework for LSGDM with uncertain and behavioral considerations. To address the behavioral uncertainty and complexity of large groups of decision-makers, this book mainly focuses on new solutions of LSGDM problems using the interval type-2 fuzzy uncertainty theory and social network analysis techniques, including the exploration of uncertain clustering analysis, the consideration of social relationships, especially trust relationships, the construction of consensus evolution networks, etc. The book is intended for researchers and postgraduates who are interested in complex group decision-making in the new media era. Authors also investigate the similar features between LSGDM problems and group recommendations to study the applications of LSGDM methods. After reading this book, readers will have a new understanding of the LSGDM study under the real complicated context. .
Introduction -- Uncertain Theory and Social Network Analysis -- Interval Type-2 Fuzzy Multi-criteria Decision-making -- Large-scale Group Decision-making with Uncertain Preferences -- Large-scale Group Decision-making with Social Relationships -- Consensus Study Considering Trust Relationships -- Consensus Evolution Networks -- Consensus Reaching Process in Large-scale Group decision-making -- Application of LSGDM Methods in Group Recommendation -- Concluding Remarks. .
Keywords: Operations research; Production management; Operations Research and Decision Theory; Operations Management